2022
DOI: 10.1371/journal.pone.0269834
|View full text |Cite
|
Sign up to set email alerts
|

Differences in self-perception of productivity and mental health among the STEMM-field scientists during the COVID-19 pandemic by sex and status as a parent: A survey in six languages

Abstract: The COVID-19 pandemic has caused unprecedented challenges for working conditions for scientists, but little is known for how the associations of these challenges with scientists’ mental health and productivity differ by sex and status as a parent. This online survey study in six languages collected data from 4,494 scientists in Science, Technology, Engineering, Mathematics, and Medicine fields across 132 countries during October–December 2021. We compared the type of challenges for work, changes in work hours,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
1
8
1
Order By: Relevance
“…Further, students experienced additional stress and anxiety due to the pandemic, which may have disproportionately affected women as female faculty spend more time performing service to the university compared to men (Suitor et al, 2001 ; Guarino and Borden, 2017 ). A survey of scientists in six languages found that work hours for teaching and administration increased during the pandemic more for women than men, and that female scholars were more concerned than men about potential negative consequences of the COVID-19 pandemic on long-term career progress and publication record (Heo et al, 2022 ). Surveys of medical faculty in the United States found that men were twice as likely as women to have accelerated productivity during the pandemic (Ellinas et al, 2022 ) and women had increased teaching load (Lufler and McNulty, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, students experienced additional stress and anxiety due to the pandemic, which may have disproportionately affected women as female faculty spend more time performing service to the university compared to men (Suitor et al, 2001 ; Guarino and Borden, 2017 ). A survey of scientists in six languages found that work hours for teaching and administration increased during the pandemic more for women than men, and that female scholars were more concerned than men about potential negative consequences of the COVID-19 pandemic on long-term career progress and publication record (Heo et al, 2022 ). Surveys of medical faculty in the United States found that men were twice as likely as women to have accelerated productivity during the pandemic (Ellinas et al, 2022 ) and women had increased teaching load (Lufler and McNulty, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The thematic analysis of this research is an effective and established method (Braun and Clarke, 2006 ; Kiger and Varpio, 2020 ) to provide a summary of the themes among the recruited study participants. Additional results on other aspects of the survey include a quantitative analysis, which we have previously provided elsewhere (Heo et al, 2022 ). Here, we focus on a qualitative, thematic analysis, and also report a summary table of the percentage of our study participants reporting each of the found themes among different geographical regions in supplementary materials (Supplementary Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Yale University Institutional Review Board. We conducted a study using an online survey questionnaire and summaries of this survey are presented elsewhere with quantitative analyses related to the mental health and well-being of scientists in STEM, medicine, public health, or other areas of science/engineering (Heo et al, 2022 ). This paper utilizes participants’ responses to an open-ended question in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Hardly surprisingly, of course, with ECRs’ productivity, the key to a successful scholarly career [ 15 18 ], so often adversely affected by the lockdowns and social-distancing characterizing the first year or so after the onset of the pandemic. Indeed, researchers were faced with a host of challenges in their efforts to work in the manner they had been accustomed to: the suspension of many lab- and field- based research activities, the general shift to remote–and often more time consuming–working practices, the dearth of opportunities for networking and collaboration, the additional caring responsibilities, the all-pervading climate of stress and the COVID-associated physical and mental health problems, to name but the most frequently cited ones [ 7 , 9 , 10 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another outcome of the pandemic likely to leave long-lasting effects is the exacerbation of existing disparities among scientists. Indeed, a host of studies evidence the disproportionate impact of the pandemic on academic work by race, disability status, academic career stage, and, most notably, by gender [ 7 9 , 19 , 20 , 23 26 ]. As the relative change in the gender gap that occurred during the pandemic has been found to be the biggest for early-career scientists [ 27 ] as well as enduring between 2020 and 2021 [ 28 ], there can be little doubt that today’s ECRs need to be prepared for further challenges ahead.…”
Section: Introductionmentioning
confidence: 99%